Soccer: process and interaction - Perl, J.; Memmert, D. (Modelling and simulation in sport and exercise, 2020)
Team Sports and the Modelling of playing processes and tactical behavior. modelling team sports is a very difficult and complex task. Although the first attempts were made in the 1950s, those early approaches were rather theoretic because of a lack of data-recording techniques and, therefore, useful data. Only since about 2010, data from team Sports such as position of players and the ball have become available and have helped to make team game modelling useful. Perl and Memmert discuss the problem of modelling complex behavior and its evaluation in the interaction of teams of players. Together with the need to reduce reality caused by a lack of usable data as well as by the restrictions of simplifying models. This leads to two central questions: - How precisely can an intentionally characterized dynamic system like a play be modeled in the first place? - What are the consequences of modelling and analysis errors for results and evaluations?